Fermented Ipil-ipil seeds (Leucaena leucocephala-lam; de wit) and its protein quality - Komari; Gatchalian, Miaflora M. (1983.)
Three trials of tempe processing were conducted in the laboratory. Results showed that on average only 255.7 grams of fresh tempe can be recovered from 500 grams of dried ipil-ipil seeds. The fresh tempe contained 87.3 grams of solids which is about 19.3% of the original seed solids. At various steps of tempe processing, it was noted that removal of the seed coat and boiling allowed for the maximum removal of mimosine. It was also observed that the steaming process significantly reduced mimosine content of the decoated seeds. Drying and mimosine fermentation, however, did not significantly affect the amount of mimosine in the seeds. Results showed that mimosine content of the raw seeds was 6.09%, while only 0.38% mimosine was found in the fresh tempe. On the average, the ipil-ipil tempe contained 15.64% protein, 7.06% fiber, 10.40% carbohydrate, 1.02% ash and 65.88% moisture. The corrected PER value of the ipil-ipil tempe was only 1.36 which is indicative of poor quality. The growth of rats fed with tempe diet showed a mean body weight of less than half of the control rats. The toxicity test, on the other hand, did not show that residual mimosine in the tempe could affect utilization of protein.
Thesis (MS Food Science)--University of the Philippines Diliman
Keywords: Leucaena -- Philippines; Lead tree -- Philippines